PENERAPAN BLENDED LEARNING BERBASIS SCAFFOLDING UNTUK MENINGATKAN KEMAMPUAN BERPIKIR LOGIS DAN HASIL BELAJAR MAHASISWA PADA MATA KULIAH BIOLOGI UMUM - Dewi Murni; Siti Romlah; Noer Hodijah (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2016)
ABSTRACTScaffolding learning approach that is applied through learning blended learning is expected to improve the student logical thinking ability. It allows students to build their own knowledge with the help of lecturers gradually. The purpose of this study was to determine the student logical thinking abilityandlearningoutcomesingeneralbiologycoursesthroughthelearningblendedlearningbased scaffolding. This research was conducted by descriptive method. Stages of research include the preparationofanevaluationinstrument,implementationoftheproductintheformofblendedlearning ingeneralbiologylectures,measurementoflogicalthinkingabilityofstudentsandlearningoutcomes evaluation stage. The results showed that there is an improvement of student logical thinking ability fromtheconcretelevelintoaformallevel.Variablecontrolingarethehighestlogicalthingkingability aspect with a percentage 81,9. The students learning outcomes also increased from lowest criteria into very good criteria with percentage29,6%.ABSTRACTScaffolding learning approach that is applied through learning blended learning is expected to improve the student logical thinking ability. It allows students to build their own knowledge with the help of lecturers gradually. The purpose of this study was to determine the student logical thinking abilityandlearningoutcomesingeneralbiologycoursesthroughthelearningblendedlearningbased scaffolding. This research was conducted by descriptive method. Stages of research include the preparationofanevaluationinstrument,implementationoftheproductintheformofblendedlearning ingeneralbiologylectures,measurementoflogicalthinkingabilityofstudentsandlearningoutcomes evaluation stage. The results showed that there is an improvement of student logical thinking ability fromtheconcretelevelintoaformallevel.Variablecontrolingarethehighestlogicalthingkingability aspect with a percentage 81,9. The students learning outcomes also increased from lowest criteria into very good criteria with percentage29,6%.Key words : General Biology, logical thinking, learning outcomes, blended learning, scaffolding